A framework for analyzing supply chain improvement - New, S (1996)
Presents a classification scheme which allows the interpretation of supply chain improvement initiatives. While there is an abundance of anecdotal evidence, there is little systematic theoretical development in the field. This is partly because of the many different ways in which co-operation between trading partners may be developed. The suggested framework is useful in that it highlights some important yet often ignored issues relating to the logic and outcomes of collaborative activities. Illustrates the use of the framework by the secondary analysis of some well-known UK examples in logistics and supply-chain management and with supplementary data gathered by questionnaire. Concludes by discussing the limitations of the scheme and its role in further research.